Concentric resistance training increases muscle strength without affecting microcirculation - Weber, Marc-André; Hildebrandt, Wulf; Schröder, Leif; Kinscherf, Ralf; Krix, Martin; Bachert, Peter; Delorme, Stefan; Essig, Marco; Kauczor, Hans-Ulrich; Krakowski-Roosen, Holger (European journal of radiology, 2010)
While the evidence is conclusive regarding the positive effects of endurance training, there is still some controversy regarding the effects of resistance training on muscular capillarity. Thus, the purpose was to assess whether resistance strength training influences resting skeletal muscle microcirculation in vivo.